That's classified! Inventing a new patent taxonomy - Stephen D. Billington; Alan J. Hanna (Queen's University Centre for Economic History (QUCEH), 2018)
Patent studies inform our understanding of innovation. Any study of patenting involves classifying patent data according to a chosen taxonomy. The literature has produced numerous taxonomies, which means patents are being classified differently across studies. This potential inconsistency is compounded by a lack of documentation provided on existing taxonomies, making them diffcult to replicate. Because of this, we develop a new patent taxonomy using machine learning techniques, and propose a new methodology to automate patent classification. We contrast existing taxonomies with our own upon a widely used patent dataset. In a regression analysis of patent classes upon patent characteristics, we show that classification bias exists: the size, statistical significance, and direction of association of coefficients depend upon how a patent dataset has been classified. We recommend investigators adopt our approach to ensure future studies are comparable and replicable.
Keywords: K11; N24; N74; O31; O33; 330; Innovation; Invention; Machine Learning; Patents; Patent Classification; Taxonomy; Economic History